2013
DOI: 10.1364/ol.38.001143
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal characterization of ultrabroadband Airy pulses

Abstract: We present experimental results of a full spatiotemporal characterization of an optical system for ultrabroadband Airy pulse generation with a liquid-crystal-on-silicon spatial light modulator. Measurements with a few micrometer spatial and almost one-wave-cycle temporal resolution were performed using a white light spatial spectral interferometry setup based on the SEA TADPOLE ultrashort pulse characterization technique. The results were compared with the theoretical model for Airy pulse propagation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
(23 reference statements)
0
8
0
Order By: Relevance
“…Attempts at producing wave packets with one transverse dimension that are propagation-invariant in media with anomalous [126] and normal [127] GVD were reported, but without verifying propagation invariance. Subsequent work was stimulated by the introduction of Airy beams [14,15], pulsed Airy beams [219][220][221][222][223], and Airy pulses [118,224]. In part, research was stimulated along the lines motivated by the Airy-Bessel wave packet reported in 2010 [118].…”
Section: After 2010mentioning
confidence: 99%
“…Attempts at producing wave packets with one transverse dimension that are propagation-invariant in media with anomalous [126] and normal [127] GVD were reported, but without verifying propagation invariance. Subsequent work was stimulated by the introduction of Airy beams [14,15], pulsed Airy beams [219][220][221][222][223], and Airy pulses [118,224]. In part, research was stimulated along the lines motivated by the Airy-Bessel wave packet reported in 2010 [118].…”
Section: After 2010mentioning
confidence: 99%
“…The spatial resolution is determined by the mode size of the fibres and is approximately 3 μm. Type II Airy beam profile was created by a reflective SLM (Holoeye LC-R 2500) with an imposed cubic phase mask in both transverse orthogonal directions [14]. The SLM was placed in the focal plane of an achromatic lens with focal length of f = 500 mm.…”
Section: Methods and Experimental Setupmentioning
confidence: 99%
“…The type of an Airy pulse is determined by properties of the optical system for creating it. It was previously shown that an SLM with a cubic phase mask containing discontinuities will produce type II Airy pulses that exhibit strong lateral dispersion [14]. For applications that require a spatially and temporally localized ultrashort pulse, type IV Airy beams would be most suitable as all its spectral components propagate along the same trajectory and their main intensity lobe is not subjected to lateral dispersion.…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…In general, a broadband 1-dimensional Airy beam can be expressed in the paraxial approximation as a superposition of its monochromatic constituents of wavenumber k over spectrum S (k) [4,5,14] .…”
Section: Theoretical Modelsmentioning
confidence: 99%
“…A spatial-spectral interferometry technique based on the SEA TADPOLE method [17] was used to fully characterize the created Airy wave field with high spatial and temporal resolution. In contrast to previous results on the spatiotemporal measurement of Airy pulses [18,19], this paper provides a more thorough comparison between Airy pulses generated using both an SLM and a custom-made cubic phase element and corresponding measurement configurations. In addition, the results of using a shorter focal length Fourier lens in the Airy generation are presented.…”
Section: Introductionmentioning
confidence: 99%